2010
DOI: 10.1002/acr.20274
|View full text |Cite
|
Sign up to set email alerts
|

Validity and responsiveness of the Michigan hand questionnaire in patients with rheumatoid arthritis: A multicenter, international study

Abstract: Objective Millions of patients suffer from the disabling hand manifestations of rheumatoid arthritis (RA), yet few hand-specific instruments are validated in this population. Our objective is to assess the reliability, validity, and responsiveness of the Michigan Hand Questionnaire (MHQ) in RA patients. Methods At enrollment and at 6 months, 128 RA patients with severe subluxation of the metacarpophalangeal joints completed the MHQ, a 37-item questionnaire with 6 domains: function, activities of daily living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 39 publications
(57 reference statements)
2
77
0
Order By: Relevance
“…However, this level of detail makes the MHQ longer than the DASH, with the questions duplicated for right and left sides. Several publications have demonstrated the reliability, validity, and responsiveness of the MHQ 57,[59][60][61][62][63] . This questionnaire is scored from 0 to 100, with 100 being the optimal score.…”
Section: Michigan Hand Outcomes Questionnairementioning
confidence: 99%
“…However, this level of detail makes the MHQ longer than the DASH, with the questions duplicated for right and left sides. Several publications have demonstrated the reliability, validity, and responsiveness of the MHQ 57,[59][60][61][62][63] . This questionnaire is scored from 0 to 100, with 100 being the optimal score.…”
Section: Michigan Hand Outcomes Questionnairementioning
confidence: 99%
“…4 The original MHQ has been used with almost all types of hand disorders and has proven to be reliable, valid, and responsive to a range of upper extremity conditions such as carpal tunnel syndrome, distal radius fracture, and rheumatoid arthritis. [5][6][7] Conversely, a validated Asian translation of MHQ is not well described, which may be restricted owing to linguistic or sociocultural differences. There is growing interest in publishing outcome studies in the field of hand surgery in Korea and in adhering to international standards by using validated outcome questionnaires.…”
mentioning
confidence: 94%
“…We found that MHQ scores were independently associated with measures of depression and coping strategies in response to nociception, with the latter accounting for most of the variability in MHQ scores. 6,10,24 A number of shortcomings of the study should be kept in mind to better interpret our data. The findings might apply best to our region and our practice setting.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,[10][11][12]18,22,23 The role of psychological factors in variation in MHQ scores is less well studied. 6,10,13,21,24 London et al noted that the mean MHQ scores were lower in patients categorized as having a high score on the Pain Catastrophizing Scale (PCS), but did not evaluate the correlation of ineffective coping strategies with hand-specific symptoms and limitations on the continuum on which they occur. 16 We undertook this study to examine the relationship between commonly used psychological measures and the MHQ in patients with upper extremity illness.…”
Section: Introductionmentioning
confidence: 99%